AIDA Model Communication Strategy On Capacity Digital Promotional Activities In Encouraging Purchasing Decisions - Ni Putu Ria Cahyaningsih; Wulan Yulianti (Institute of Computer Science (IOCS), 2024)
This research aims to find out the stages of CAKAP's digital promotional activities in forming a strategy that can encourage their consumers' purchasing decisions and have an impact on returning turnover. The theoretical model used is the theory from Philips D.M (2023). The AIDA model is used to understand the processes and stages in encouraging purchasing activities. As well as the four stages, namely: Awareness (Awareness), Interest (Interest), Desire (Desire), and Action (Action). This research is a qualitative research approach with descriptive methods. The data collection technique used was direct interviews by asking questions directly to CAKAP internal parties and CAKAP external parties. The research results contain the first stage of CAKAP in building awareness through education and planning follow-up promotions to be shared on social media. The second stage increases curiosity (interest) by CAKAP sharing content with members and creating WhatsApp statuses which are expected to raise questions. The third stage fosters a sense of curiosity (desire). CAKAP utilizes the FOMO trend for this. The final stage is taking CAKAP action to convince members of the benefits obtained from CAKAP and CAKAP products. This research states that the stages of each element of the AIDA model help CAKAP to encourage purchasing decisions